Market Reaction to Cabinet Reshuffle: The Indonesian Evidence - Supramono, Supramono; Wilis, Widhiastuti; Utami, I. (International Journal of Economics and Financial Issues, 2017)
This event study investigates the Indonesian capital market reaction to the announcement of cabinet reshuffle as a major political event in Indonesia. We also detect the possibility of size effect anomaly related to this political event. Consequently, we not only study 43 large-capitalization firms that are classified into LQ 45 index but also 26 small-capitalization shares. Our findings show that there is no significant abnormal return surrounding the announcement date. We conclude that the announcement of cabinet reshuffle does not contain information value to the market and does not cause size effect. Keywords: event study, market reaction, size effect, cabinet reshuffle, abnormal return. JELClassification: M2